PROPERTIES AND COMPUTER SIMULATION OF ELECTROMAGNETIC FIELD UNIFORM TRAFFIC CHARGED PARTICLE - Konoval, O.A. (Journal of Information Technologies in Education (ITE), 2010)
In the article described the method of teaching electrodynamics, which is based on considerably fewer independent source principles (Coulomb’s law, the principle of relativity and the principle of superposition). Based on a description and analysis of the interaction of moving charged particles.